Investigating the combined effects of heat and lighting on students reaction time in laboratory condition - Zohre Mohebian; Younes Mehrifar; Habibollah Dehghan; Ehsanollah Habibi; Ghasem Yadegarfar (Muhandisī-i bihdāsht-i ḥirfah/ī, 2016)
Introduction: In many workplaces there is exposure to heat and light simultaneously. This study investigated the combined effect of heat and lighting on some cognitive performance, i.e. reaction time.